Angiography-Derived vs Wire-Based Physiological Assessment in Coronary Artery Disease: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Muhammad Mudasir; Abdul Rehman; Muhammad Ibrahim Rashid; Mohammad Salah; Muhammad Jawad; Ramesha Tahir; Raja Muhammad Umer; Prem Kumar; Rohin Kumar (Critical Pathways in Cardiology: A Journal of Evidence-Based Medicine, 2026)
This study aimed to determine whether angiography-based physiological assessment yields clinical outcomes comparable to those of conventional wire-based pressure measurements in patients with coronary artery disease (CAD) undergoing evaluation of intermediate coronary stenoses. A systematic literature search was conducted in PubMed, Embase, and the Cochrane Central Register of Controlled Trials through April 12, 2026. Randomized controlled trials comparing angiography-derived indices (such as QFR, vFFR, and angiography-based FFR) with standard wire-based methods (FFR/iFR) were included. Pooled risk ratios (RR) with 95% confidence intervals (CI) were calculated using a random-effects model, and heterogeneity was evaluated using the I² statistic. A total of three randomized trials involving 6,141 participants were included, with 3,089 patients assigned to angiography-derived assessment. At 12 months, no statistically significant difference was observed in major adverse cardiovascular events between the two strategies (RR 1.14; 95% CI 0.58–2.25; P =.48). Additionally, outcomes including all-cause mortality, myocardial infarction, target vessel failure, repeat revascularization, stent thrombosis, stroke, and cardiac mortality were comparable across groups (all P >.05). Angiography-derived physiological assessment provides similar short-term clinical outcomes to traditional wire-based techniques, supporting its use as a less invasive alternative for assessing intermediate coronary lesions. Larger studies with extended follow-up are needed to confirm these findings.